2015
DOI: 10.1016/j.imlet.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular pH and hypoxia on the function and development of antigen-specific cytotoxic T lymphocytes

Abstract: The major effector cells for cellular adaptive immunity are CD8(+) cytotoxic T lymphocytes (CTLs), which can recognize and kill virus-infected cells and tumor cells. Although CTLs exhibit strong cytolytic activity against target cells in vitro, a number of studies have demonstrated that their function is often impaired within tumors. Nevertheless, CTLs can regain their cytotoxic ability after escaping from the tumor environment, suggesting that the milieu created by tumors may affect the function of CTLs. As f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 39 publications
7
78
1
Order By: Relevance
“…Furthermore, as tumors outgrow their blood supply and form hypoxic regions, reliance on glycolysis as a primary mode of glucose metabolism leads to microenvironment acidification through accumulation of lactic acid. Acidic TME affects immune cell polarization, decreasing antitumor immunity, disrupting T‐cell motility, and causing loss of cytotoxic function in CD8+T cells . Furthermore, lactate metabolism in oxygenated cancer cells has been shown to increase glutaminolysis , further promoting competition for resources between cancer and immune cells, the outcome of which can determine not only the function but also composition of immune cells in the TME.…”
Section: Immunometabolismmentioning
confidence: 99%
“…Furthermore, as tumors outgrow their blood supply and form hypoxic regions, reliance on glycolysis as a primary mode of glucose metabolism leads to microenvironment acidification through accumulation of lactic acid. Acidic TME affects immune cell polarization, decreasing antitumor immunity, disrupting T‐cell motility, and causing loss of cytotoxic function in CD8+T cells . Furthermore, lactate metabolism in oxygenated cancer cells has been shown to increase glutaminolysis , further promoting competition for resources between cancer and immune cells, the outcome of which can determine not only the function but also composition of immune cells in the TME.…”
Section: Immunometabolismmentioning
confidence: 99%
“…Similarly, other in vivo studies demonstrate preferential localization of T cells away from hypoxic tumor zones, suggesting a possible immune escape mechanism used by tumor cells (20)(21)(22). However, some studies have demonstrated that T cells are better killers when activated at lower than normal oxygen conditions (23) and that such cells can enhance tumor rejection (24)(25)(26)(27). Additionally, another study demonstrated increased production of the lytic molecules perforin and granzyme upon constitutive activation of hypoxia inducible factor-1 (HIF-1), the predominate transcription factor for hypoxia signaling, indicating that hypoxic T cells are better killers (28,29).…”
Section: Introductionmentioning
confidence: 94%
“…6,9,[57][58][59] Inflammatory cells however are more resilient to such conditions and can infiltrate the hematoma. [60][61][62] Once inside the hematoma, inflammatory cells send signals to attract other cell types (e.g. mesenchymal cells) to migrate to the zone of injury.…”
Section: The Fracture Hematomamentioning
confidence: 99%